Olefin Polymers
A low-density olefin polymer with introduced highly crystalline regions, produced using a metallocene catalyst, addresses compatibility issues with polar materials, achieving improved mechanical properties and adhesion.
Patent Information
- Application Number
- JP2023523278
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-23
- Filing Date
- 2022-03-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-03-23
AI Technical Summary
Polyolefins, particularly polyethylene, lack compatibility with polar resins and metals due to the absence of polar groups, leading to low adhesion and poor surface hydrophilicity, and existing methods for introducing polar groups result in intramolecular crosslinking, molecular chain scission, and poor miscibility.
A low-density olefin polymer is produced by polymerizing olefin monomers with hydrogen gas in the presence of a specific metallocene catalyst composition, introducing highly crystalline regions to enhance mechanical rigidity and compatibility with polar materials.
The olefin polymer exhibits high mechanical rigidity, improved tensile strength, flexural modulus, and hardness, with enhanced compatibility and reduced ultra-low crystallinity, suitable for various applications.
Smart Images

Figure 0007612277000001 
Figure 0007612277000002 
Figure 0007612277000003
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean patent application No. 10-2021-0037280 filed on March 23, 2021, the entire contents of which are incorporated herein by reference. The present invention relates to an olefin polymer. [Background technology]
[0002] Polyolefins are excellent in moldability, heat resistance, mechanical properties, sanitary quality, water vapor permeability resistance, and appearance properties of molded products, and are widely used for extrusion molded products, blow molded products, and injection molded products. However, polyolefins, especially polyethylene, have a problem that they have low compatibility with polar resins such as nylon and low adhesion to polar resins and metals because they do not have polar groups in their molecules. As a result, it has been difficult to blend polyolefins with polar resins or metals or to laminate them with these materials. In addition, molded products of polyolefins have a problem that their surface hydrophilicity and antistatic properties are low.
[0003] To solve these problems and increase the affinity for polar materials, a method of grafting a polar group-containing monomer onto a polyolefin by radical polymerization has been widely used. However, this method has the problem that intramolecular crosslinking and molecular chain scission of the polyolefin occur during the grafting reaction, resulting in poor viscosity balance between the graft polymer and the polar resin, and low miscibility. In addition, there is a problem that the appearance characteristics of the molded product are poor due to gel components generated by intramolecular crosslinking or foreign matter generated by molecular chain scission.
[0004] In addition, as a method for producing an olefin polymer such as an ethylene homopolymer, an ethylene / α-olefin copolymer, a propylene homopolymer, or a propylene / α-olefin copolymer, a method for copolymerizing a polar monomer in the presence of a metal catalyst such as a titanium catalyst or a vanadium catalyst has been used. However, when a polar monomer is copolymerized using such a metal catalyst, there are problems in that the molecular weight distribution or composition distribution is broad and the polymerization activity is low.
[0005] As another method, a method of polymerization in the presence of a metallocene catalyst consisting of a transition metal compound such as zirconocene dichloride and an organoaluminum oxy compound (aluminoxane) is known. When a metallocene catalyst is used, a highly active high molecular weight olefin polymer is obtained, and the produced olefin polymer has a narrow molecular weight distribution and a narrow composition distribution.
[0006] In addition, a method using a metallocene catalyst is also known as a method for producing a polyolefin containing a polar group using a metallocene compound having a ligand of an unbridged cyclopentadienyl group, a bridged or unbridged bisindenyl group, or an ethylene-bridged unsubstituted indenyl group / fluorenyl group as a catalyst. However, these methods have a disadvantage in that the polymerization activity is very low. Therefore, a method of protecting the polar group with a protecting group is carried out, but when a protecting group is introduced, the protecting group must be removed after the reaction, which causes a problem of complicated processes.
[0007] Ansa-metallocene compounds are organometallic compounds that contain two ligands linked together by a bridge group that prevents rotation of the ligands and determines the activity and structure of the metal center.
[0008] Such ansa-metallocene compounds are used as catalysts in the production of olefin homopolymers or copolymers. In particular, ansa-metallocene compounds containing cyclopentadienyl-fluorenyl ligands are known to be capable of producing high molecular weight polyethylene, thereby controlling the microstructure of polypropylene.
[0009] In addition, ansa-metallocene compounds containing an indenyl ligand are known to be capable of producing polyolefins with excellent activity and improved stereoregularity.
[0010] Thus, various studies have been conducted on ansa-metallocene compounds that have higher activity and can control the microstructure of olefin polymers, but the extent of the research is still insufficient. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Korean Patent Publication No. 2007-0003071 Summary of the Invention [Problem to be solved by the invention]
[0012] An object of the present invention is to provide a low-density olefin polymer having high crystalline domains introduced therein and exhibiting high mechanical rigidity. [Means for solving the problem]
[0013] In order to solve the above problems, the present invention provides an olefin polymer that satisfies the following requirements (1) to (4). (1) A melt index (190°C, 2.16 kg load condition) of 0.1 to 10.0 g / 10 min. (2) The density is 0.875 to 0.895 g / cc; (3) the elution temperature (Te) measured by cross-fractionation chromatography (CFC) is 30 to 40°C; (4) When CFC is measured, P(75)-P(50) is 8.0 or less and P(75)-P(50) is 12.0 or less. Here, P(75) and P(50) are the elution amounts (wt%) in the temperature range of -20 to 75°C and -20 to 50°C in the temperature-elution amount graph measured with CFC, respectively. Effect of the Invention
[0014] The olefin polymer according to the present invention is a low-density olefin polymer having highly crystalline regions introduced therein, and exhibits high mechanical rigidity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will now be described in more detail to aid in understanding the invention. The terms and words used in the description of the present invention and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0016] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerization of the same or different types of monomers. The generic term "polymer" includes the terms "homopolymer", "copolymer", "terpolymer" and "hybrid polymer". The term "hybrid polymer" refers to a polymer prepared by polymerization of two or more different types of monomers. The generic term "hybrid polymer" includes the term "copolymer" (usually used to refer to a polymer prepared from two different types of monomers) as well as the term "terpolymer" (usually used to refer to a polymer prepared from three different types of monomers). This includes polymers prepared by polymerization of four or more types of monomers.
[0017] The olefin polymer according to the present invention is characterized by satisfying the following requirements (1) to (5). (1) A melt index (190°C, 2.16 kg load condition) of 0.1 to 10.0 g / 10 min. (2) The density is 0.875 to 0.895 g / cc; (3) the elution temperature (Te) measured by cross-fractionation chromatography (CFC) is 30 to 40°C; (4) When CFC is measured, P(75)-P(50) is 8.0 or less and P(75)-P(50) is 12.0 or less. Here, P(75) and P(50) are the elution amounts (wt%) in the temperature range of -20 to 75°C and -20 to 50°C in the temperature-elution amount graph measured with CFC, respectively.
[0018] The olefin polymer according to the present invention has a low density, and has a high crystallinity region introduced therein, compared with conventional olefin polymers, and exhibits higher tensile strength, flexural modulus, and hardness when it has the same level of density and melt index (Melt Index, 190°C, 2.16 kg load condition). The olefin polymer according to the present invention is produced by a production method including a step of polymerizing an olefin monomer while introducing hydrogen gas in the presence of an olefin polymerization catalyst composition, and the introduction of a high crystallinity region by the introduction of hydrogen gas during polymerization exhibits excellent mechanical rigidity.
[0019] The olefin polymer satisfies the requirement that (1) it has a melt index (MI, under conditions of 190° C. and a load of 2.16 kg) of 0.1 to 10.0 g / 10 min. The melt index (MI) can be adjusted by adjusting the amount of catalyst used in the polymerization process of an olefin polymer relative to a comonomer, and affects the mechanical properties, impact strength, and moldability of the olefin polymer.
[0020] The melt index is measured under low density conditions of 0.875 to 0.895 g / cc in accordance with ASTM D1238 at 190° C. and a load of 2.16 kg, and is 0.1 to 10.0 g / 10 minutes. Specifically, it may be 0.3 g / 10 minutes or more, 0.4 g / 10 minutes or more, and 9.0 g / 10 minutes or less, or 7.0 g / 10 minutes or less.
[0021] The olefin polymer satisfies the requirement (2) that the density is 0.875 to 0.895 g / cc. Specifically, the density may be 0.876 g / cc or more, 0.878 g / cc or more, 0.892 g / cc or less, or 0.891 g / cc or less.
[0022] Generally, the density of an olefin polymer is affected by the type and content of the monomer used in polymerization, the degree of polymerization, etc., and in the case of a copolymer, it is greatly affected by the content of the comonomer. The olefin polymer of the present invention is polymerized using a catalyst composition containing a transition metal compound having a characteristic structure, and it is possible to introduce a large amount of comonomer, and it can have a low density in the above range.
[0023] The olefin polymer satisfies the requirement (3) that the elution temperature (Te) measured by cross-fractionation chromatography (CFC) is 30 to 40° C. Specifically, the elution temperature may be 31° C. or more, 32° C. or more, and 40° C. or less, or 39° C. or less.
[0024] The olefin polymer satisfies the requirement (4) that, in the CFC measurement, 8.0≦P(75)−P(50)≦12.0. Here, P(75) and P(50) are the elution amounts (wt%) in the temperature range of -20 to 75°C and -20 to 50°C in the temperature-elution amount graph measured with CFC, respectively.
[0025] The fact that P(75) and P(50) satisfy the range of the above requirement (4) means that the olefin polymer has a high crystallinity content in the temperature range. The olefin polymer of the present invention has a high crystallinity content compared to a polymer having a similar elution temperature (Te), and therefore the crosslinking foaming efficiency is increased, and thus a foam having excellent mechanical properties can be produced.
[0026] When P(75) and P(50) are outside the range of the above requirement (4), the mechanical properties of the olefin polymer may be deteriorated. As described later, P(75) and P(50) satisfy the range of the requirement (4) by feeding hydrogen at 20 to 100 cc / min during the polymerization of ethylene and α-olefin monomers in the present invention. Specifically, when hydrogen is fed at the above content, the polymerization reaction is terminated at a constant rate, and the molecular weight distribution and crystallinity distribution are adjusted to a constant level, thereby satisfying the range corresponding to the requirement (4).
[0027] The olefin polymer has a melt index (MI 2.16 , 190℃, 2.16kg load) 10 , 190℃, 10kg load condition) value (MI 10 / MI 2.16 (5) Melt flow rate ratio (MFRR, Melt flow rate ratio, MI 10 / MI 2.16 ) is 5 to 10, and the melt flow rate ratio may specifically be 6 or more and 9 or less, or 8 or less.
[0028] The melt flow rate ratio can exhibit a low value as required by the above requirement (5) by reducing the number of long side chains (LCB) in the olefin polymer, and the mechanical properties of the polymer can be improved.
[0029] The olefin polymer can also satisfy the requirement (6) that the melting temperature (Tm) measured by a differential scanning calorimeter (DSC) is 55 to 90°C. Specifically, the melting temperature (Tm) may be 60°C or more, 65°C or more, and 80°C or less, or 75°C or less, i.e., 60°C≦Tm≦80°C, more specifically, 65°C≦Tm≦75°C.
[0030] The olefin polymer may further satisfy the requirement (7) that the glass transition temperature (Tg) measured by a differential scanning calorimeter (DSC) is −70 to −30° C., and specifically, the glass transition temperature (Tg) may be −60° C. or more, −51° C. or more, and −43° C. or less.
[0031] Generally, the melting temperature (Tm) is measured using a differential scanning calorimeter (DSC) by heating at a constant rate to a temperature about 30°C higher than the melting temperature (Tm) and then cooling at a constant rate to a temperature about 30°C lower than the glass transition temperature (Tg) in the first cycle, followed by obtaining a standard melting temperature (Tm) peak in the second cycle.
[0032] The measurement by the differential scanning calorimeter precision measurement method (SSA) is widely known as a method for obtaining more precise crystal information by using a differential scanning calorimeter (DSC) to repeat a process of heating and cooling to a temperature just before the peak of the melting temperature (Tm) after the first cycle, followed by a process of heating and cooling to a temperature about 5°C lower.
[0033] When a small amount of highly crystalline regions is introduced into an olefin polymer, the melting temperature is not measured using a general differential scanning calorimeter (DSC), but a high-temperature melting peak can be measured using the above-mentioned differential scanning calorimeter precision measurement method (SSA).
[0034] In addition, the olefin polymer according to one example of the present invention may further satisfy the requirement (8) that the weight average molecular weight (Mw) is 10,000 to 500,000 g / mol. Specifically, the weight average molecular weight (Mw) may be 30,000 g / mol or more, 50,000 g / mol or more, 300,000 g / mol or less, or 200,000 g / mol or less.
[0035] The weight average molecular weight (Mw) is a polystyrene-equivalent molecular weight analyzed by gel permeation chromatography (GPC).
[0036] In addition, the olefin polymer according to one embodiment of the present invention may further satisfy the requirement that (9) molecular weight distribution (MWD), which is the ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn), is 0.1 to 6.0. Specifically, the molecular weight distribution (MWD) may be 1.0 or more, 2.0 or more, 4.0 or less, or 3.0 or less.
[0037] Moreover, the olefin polymer according to one embodiment of the present invention can further satisfy the requirement (10) that the soluble fraction (SF) at −20° C. is 2% by weight or less when measured by cross fractionation chromatography (CFC). Specifically, the soluble fraction may be 2% by weight or less, or 1% by weight or less.
[0038] The lower the temperature at which a fraction elutes during cross-fractionation chromatography (CFC), the lower the crystallinity. The soluble fraction (SF) eluting at -20°C or lower during cross-fractionation chromatography (CFC) can be considered as an ultra-low crystallinity region.
[0039] Generally, the lower the density of a polymer, the lower the crystallinity, and the more the ultra-low crystalline region, resulting in improved impact strength. However, in a typical olefin-based polymer, when the ultra-low crystalline region exceeds a certain level, the mechanical properties deteriorate. The olefin-based polymer according to the present invention has a polycrystalline structure, and by reducing the ultra-low crystalline content and relatively increasing the high crystalline content, it is possible to exhibit excellent mechanical properties such as improved tensile strength, tear strength, and flexural modulus.
[0040] The olefin polymer may be a homopolymer of an olefin monomer, specifically, any one selected from an α-olefin monomer, a cyclic olefin monomer, a diene olefin monomer, a triene olefin monomer, and a styrene monomer, or a copolymer of two or more of them. More specifically, the olefin polymer may be a copolymer of ethylene and an α-olefin having 3 to 12 carbon atoms, or a copolymer of ethylene and an α-olefin having 3 to 10 carbon atoms.
[0041] The α-olefin comonomer may be one or more selected from the group consisting of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, vinylnorbornene, 1,4-butadiene, 1,5-pentadiene, 1,6-hexadiene, styrene, α-methylstyrene, divinylbenzene, and 3-chloromethylstyrene.
[0042] More specifically, the olefin-based polymer according to an example of the present invention may be a copolymer of ethylene and propylene, ethylene and 1-butene, ethylene and 1-hexene, ethylene and 4-methyl-1-pentene, or ethylene and 1-octene, and more specifically, the olefin-based polymer according to an example of the present invention may be a copolymer of ethylene and 1-butene.
[0043] When the olefin-based polymer is a copolymer of ethylene and an α-olefin, the amount of the α-olefin may be 90% by weight or less, more specifically 70% by weight or less, even more specifically 5% by weight to 60% by weight, and even more specifically 10% by weight to 50% by weight, based on the total weight of the copolymer. When the α-olefin is contained in the above range, the above-mentioned physical properties can be appropriately realized.
[0044] The olefin polymer according to the present invention having the above physical properties and structural characteristics can be prepared by a continuous solution polymerization reaction in which an olefin monomer is polymerized in a single reactor while feeding hydrogen gas in the presence of a metallocene catalyst composition containing one or more transition metal compounds. Thus, the olefin polymer according to the present invention does not form a block in which two or more repeat units derived from any one of the monomers constituting the polymer are linearly linked. That is, the olefin polymer according to the present invention does not include a block copolymer, and may be selected from the group consisting of a random copolymer, an alternating copolymer, and a graft copolymer, and more specifically, may be a random copolymer.
[0045] Specifically, the olefin copolymer of the present invention can be prepared by a method including a step of polymerizing an olefin monomer while feeding hydrogen gas at 20 to 100 cc / min in the presence of an olefin polymerization catalyst composition comprising a transition metal compound represented by the following formula 1, for example, by a continuous solution polymerization reaction using a continuous stirred tank reactor by feeding hydrogen in the presence of an olefin polymerization catalyst composition comprising a transition metal compound represented by the following formula 1:
[0046] However, in the production of an olefin-based polymer according to one embodiment of the present invention, the scope of the structure of the transition metal compound of the following chemical formula 1 is not limited to the specific disclosed form, but should be understood to include all modifications, equivalents, or alternatives within the spirit and technical scope of the present invention.
[0047] [ka]
[0048] In the above Chemical Formula 1, R1's may be the same or different and each independently represent a metalloid group of a Group 4 metal substituted with hydrogen, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group, a silyl group, an alkylaryl group, an arylalkyl group, or a hydrocarbyl group, and the two R1's may be linked to each other to form a ring through an alkylidyne group containing an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms; R2 are the same or different and each independently represent hydrogen; halogen; alkyl having 1 to 20 carbon atoms; aryl; alkoxy; aryloxy; or an amido group, and two or more of R2 may be bonded to each other to form an aliphatic ring or an aromatic ring; R3 are the same or different, and each independently represent a nitrogen-containing aliphatic or aromatic ring substituted or unsubstituted with hydrogen, halogen, an alkyl group having 1 to 20 carbon atoms, or an aryl group, and when there are a plurality of the substituents, two or more of the substituents may be bonded to each other to form an aliphatic or aromatic ring; M is a group 4 transition metal; Q1 and Q2 each independently represent a halogen; an alkyl group having 1 to 20 carbon atoms; an alkenyl group; an aryl group; an alkylaryl group; an arylalkyl group; an alkylamide group having 1 to 20 carbon atoms; an arylamide group; or an alkylidene group having 1 to 20 carbon atoms.
[0049] In another embodiment of the present invention, in the above-mentioned chemical formula 1, R1 and R2 may be the same or different, and each independently may be hydrogen; alkyl having 1 to 20 carbon atoms; aryl; or silyl;
[0050] R3 may be the same or different, and may be an alkyl having 1 to 20 carbon atoms; an alkenyl having 2 to 20 carbon atoms; an aryl; an alkylaryl; an arylalkyl; an alkoxy having 1 to 20 carbon atoms; an aryloxy; or an amide; and two or more of R6 may be bonded to each other to form an aliphatic or aromatic ring;
[0051] wherein Q1 and Q2 are the same or different and each independently represents a halogen; an alkyl having 1 to 20 carbon atoms; an alkylamide having 1 to 20 carbon atoms; or an arylamide; M may be a Group 4 transition metal.
[0052] The transition metal compound represented by the formula 1 has a feature that the metal sites are connected by a cyclopentadienyl ligand to which tetrahydroquinoline is introduced, and structurally, the Cp-MN angle is narrow, and the Q1-M-Q2 (Q3-M-Q4) angle where the monomers approach is wide. In addition, the Cp, tetrahydroquinoline, nitrogen, and metal sites are sequentially connected by a cyclic bond to form a more stable and solid pentagonal ring structure. Therefore, when such a compound is activated by reacting it with a cocatalyst such as methylaluminoxane or B(C6F5)3 and then applied to olefin polymerization, an olefin polymer having characteristics such as high activity, high molecular weight, and high copolymerizability can be polymerized even at a high polymerization temperature.
[0053] In the step of polymerizing the olefin monomer, the amount of hydrogen gas fed may be 20 to 40 sccm, specifically 22 to 38 sccm, and more specifically 22 to 35 sccm. The amount of hydrogen gas fed is based on the amount of ethylene fed to the reaction system at 0.87 kg / h. When the amount of hydrogen gas fed satisfies the above range in the presence of a catalyst composition for olefin polymerization containing a transition metal compound of Chemical Formula 1, an olefin polymer satisfying the physical property range requirements of the olefin polymer according to one embodiment of the present invention can be produced.
[0054] Each of the substituents defined in this specification is explained in detail below. As used herein, unless otherwise specified, the term "hydrocarbyl group" refers to a monovalent hydrocarbon group having 1 to 20 carbon atoms and consisting only of carbon and hydrogen, such as alkyl, aryl, alkenyl, alkynyl, cycloalkyl, alkylaryl, or arylalkyl, regardless of its structure.
[0055] The term "halogen" as used herein, unless otherwise specified, means fluorine, chlorine, bromine, or iodine. The term "alkyl", as used herein, unless otherwise specified, means a straight or branched chain hydrocarbon residue.
[0056] As used herein, unless otherwise noted, the term "cycloalkyl" refers to cyclic alkyl, including cyclopropyl and the like. As used herein, unless otherwise specified, the term "alkenyl" means either a straight or branched chain alkenyl group.
[0057] The branched chain may be an alkyl having 1 to 20 carbon atoms; an alkenyl having 2 to 20 carbon atoms; an aryl having 6 to 20 carbon atoms; an alkylaryl having 7 to 20 carbon atoms; or an arylalkyl having 7 to 20 carbon atoms.
[0058] The term "aryl" as used herein, unless otherwise specified, refers to an aromatic group having 6 to 20 carbon atoms, and specific examples thereof include phenyl, naphthyl, anthryl, phenanthryl, chrysenyl, pyrenyl, anthracenyl, pyridyl, dimethylanilinyl, and anisolyl, but are not limited to these examples.
[0059] The alkylaryl group refers to an aryl group substituted with an alkyl group. The arylalkyl group refers to an alkyl group substituted with an aryl group.
[0060] The ring (or heterocyclic group) means a monovalent aliphatic or aromatic hydrocarbon group having a ring atom of 5 to 20 carbon atoms and containing one or more heteroatoms, and may be a single ring or a condensed ring of two or more rings. The heterocyclic group may or may not be substituted with an alkyl group. Examples of such a group include indoline and tetrahydroquinoline, but the present invention is not limited to these.
[0061] The alkylamino group means an amino group substituted with the alkyl group, and examples thereof include a dimethylamino group and a diethylamino group, but are not limited to these examples.
[0062] According to one embodiment of the present invention, the aryl group preferably has 6 to 20 carbon atoms, and specific examples thereof include, but are not limited to, phenyl, naphthyl, anthracenyl, pyridyl, dimethylanilinyl, and anisolyl.
[0063] In this specification, silyl may be unsubstituted or substituted with alkyl having 1 to 20 carbon atoms, and examples thereof include silyl, trimethylsilyl, triethylsilyl, tripropylsilyl, tributylsilyl, trihexylsilyl, triisopropylsilyl, triisobutylsilyl, triethoxysilyl, triphenylsilyl, tris(trimethylsilyl)silyl, and the like, but are not limited to these.
[0064] The transition metal compound of Formula 1 may be, but is not limited to, the following Formula 1-1:
[0065] [ka] In addition, compounds having various structures within the scope defined in Chemical Formula 1 may be used.
[0066] The transition metal compound of the formula 1 can introduce a large amount of α-olefin as well as low density polyethylene due to the structural characteristics of the catalyst, so that it is possible to produce low density olefin polymers of 0.850g / cc to 0.890g / cc level.
[0067] The transition metal compound of Formula 1 can be prepared, for example, by the following method.
[0068] [ka]
[0069] In the reaction formula 1, R1 to R3, M, Q1, and Q2 are the same as those in the chemical formula 1.
[0070] The compound of Formula 1 can be prepared by the method described in Korean Patent Publication No. 2007-0003071, the contents of which are incorporated herein in their entirety.
[0071] The transition metal compound of Formula 1 may be used as a polymerization catalyst in the form of a composition further including one or more of the cocatalyst compounds represented by Formulas 2, 3, and 4 below.
[0072] [Chemical formula 2] -[Al(R4)-O] a -
[0073] [Chemical formula 3] A(R4)3
[0074] [Chemical formula 4] [LH] + [W(D)4] - or [L] + [W(D)4] -
[0075] In the above Chemical Formulas 2 to 3, R4 may be the same or different, and each R4 is independently selected from the group consisting of halogen, hydrocarbyl having 1 to 20 carbon atoms, and hydrocarbyl substituted with halogen having 1 to 20 carbon atoms; A is aluminum or boron; D's each independently represent an aryl having 6 to 20 carbon atoms or an alkyl having 1 to 20 carbon atoms in which one or more hydrogen atoms can be substituted by a substituent, and in this case, the substituent is at least one selected from the group consisting of a halogen, a hydrocarbyl having 1 to 20 carbon atoms, an alkoxy having 1 to 20 carbon atoms, and an aryloxy having 6 to 20 carbon atoms; H is a hydrogen atom, L is a neutral or cationic Lewis base; W is a group 13 element; a is an integer of 2 or greater.
[0076] Examples of the compound represented by Chemical Formula 2 include alkylaluminoxanes such as methylaluminoxane (MAO), ethylaluminoxane, isobutylaluminoxane, and butylaluminoxane, and also include modified alkylaluminoxanes in which two or more of the alkylaluminoxanes are mixed, specifically, methylaluminoxane and modified methylaluminoxane (MMAO).
[0077] Examples of the compound represented by Chemical Formula 3 include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylchloroaluminum, triisopropylaluminum, tri-s-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylaluminum methoxide, dimethylaluminum ethoxide, trimethylboron, triethylboron, triisobutylboron, tripropylboron, and tributylboron. Specifically, the compound may be selected from among trimethylaluminum, triethylaluminum, and triisobutylaluminum.
[0078] Examples of the compound represented by the chemical formula 4 include triethylammonium tetraphenylboron, tributylammonium tetraphenylboron, trimethylammonium tetraphenylboron, tripropylammonium tetraphenylboron, trimethylammonium tetra(p-tolyl)boron, trimethylammonium tetra(o,p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, trimethylammonium tetra(p-trifluoromethylphenyl)boron, tributylammonium tetrapentafluorophenylboron, N,N-diethylanilinium tetraphenylboron, N,N-diethylanilinium tetrapentafluorophenylboron, diethylammonium tetrapentafluorophenylboron, triphenylphosphonium tetraphenylboron, trimethylphosphonium tetraphenylboron, dimethylanilinium tetrakis(pentafluorophenyl)borate, triethylammonium tetraphenylaluminum, tributary n-Diethylanilinium tetraphenylaluminum, n-Diethylanilinium tetrapentafluorophenylaluminum, n-Diethylanilinium tetrapentafluorophenylaluminum, n-Diethylanilinium tetrapentafluorophenylaluminum, n-Diethylanilinium tetrapentafluorophenylaluminum, n-Diethylammonium tetrapentatetra ...p-dimethylphenyl)boron, triphenylcarbonium tetra(p-trifluoromethylphenyl)boron, or triphenylcarbonium tetrapentafluorophenylboron.
[0079] The catalyst composition may be prepared as a first method by a method including the steps of: 1) contacting a transition metal compound represented by Chemical Formula 1 with a compound represented by Chemical Formula 2 or Chemical Formula 3 to obtain a mixture; and 2) adding a compound represented by Chemical Formula 4 to the mixture.
[0080] In addition, the catalyst composition can be prepared by a second method in which the transition metal compound represented by Formula 1 is contacted with the compound represented by Formula 4.
[0081] In the case of the first method of the method for producing the catalyst composition, the molar ratio of the transition metal compound represented by the formula 1 and the compound represented by the formula 2 / the compound represented by the formula 2 or the formula 3 may be 1 / 5,000 to 1 / 2, specifically 1 / 1,000 to 1 / 10, and more specifically 1 / 500 to 1 / 20. When the molar ratio of the transition metal compound represented by the formula 1 / the compound represented by the formula 2 or the formula 3 exceeds 1 / 2, there is a problem that the amount of the alkylating agent is very small, so that the alkylation of the metal compound is not completely performed. When the molar ratio is less than 1 / 5,000, although the alkylation of the metal compound is performed, there is a problem that the activation of the alkylated metal compound is not completely performed due to a side reaction between the remaining excess alkylating agent and the activating agent, which is the compound of the formula 4. In addition, the molar ratio of the transition metal compound represented by the formula 1 / the compound represented by the formula 4 may be 1 / 25 to 1, specifically 1 / 10 to 1, and more specifically 1 / 5 to 1. When the molar ratio of the transition metal compound represented by Formula 1 / the compound represented by Formula 4 exceeds 1, the activation of the metal compound is not complete due to a relatively small amount of the activator, and the activity of the resulting catalyst composition may be reduced. When the molar ratio is less than 1 / 25, the activation of the metal compound is complete, but the unit price of the catalyst composition may be uneconomical or the purity of the resulting polymer may be reduced due to the remaining excess activator.
[0082] In the second method of preparing the catalyst composition, the molar ratio of the transition metal compound represented by Formula 1 to the compound represented by Formula 4 may be 1 / 10,000 to 1 / 10, specifically 1 / 5,000 to 1 / 100, and more specifically 1 / 3,000 to 1 / 500. If the molar ratio exceeds 1 / 10, the amount of activator is relatively small, so that activation of the metal compound cannot be completed, and the activity of the catalyst composition produced may be reduced. If the molar ratio is less than 1 / 10,000, the activation of the metal compound is completed, but the unit price of the catalyst composition may be uneconomical or the purity of the polymer produced may be reduced due to the remaining excess activator.
[0083] When preparing the catalyst composition, a hydrocarbon solvent such as pentane, hexane, or heptane, or an aromatic solvent such as benzene or toluene may be used as a reaction solvent.
[0084] The catalyst composition may contain the transition metal compound and the promoter compound supported on a carrier. The carrier can be used without any particular limitation as long as it is used as a carrier in a metallocene catalyst. Specifically, the carrier can be silica, silica-alumina, silica-magnesia, or the like, or a mixture of any one or more of these can be used.
[0085] In particular, when the support is silica, the silica support and the functional group of the metallocene compound of the chemical formula 1 form a chemical bond, so that there is almost no catalyst liberated from the surface during the olefin polymerization process. As a result, it is possible to prevent fouling, which is caused by entanglement of the reactor wall or polymer particles, during the olefin polymer production process. In addition, the olefin polymer produced in the presence of a catalyst containing the silica support has excellent polymer particle morphology and apparent density.
[0086] More specifically, the support may be silica or silica-alumina that has been dried at a high temperature and that contains highly reactive siloxane groups on the surface thereof by a method such as high-temperature drying. The support may further include an oxide, carbonate, sulfate, or nitrate component, such as Na2O, K2CO3, BaSO4, or Mg(NO3)2.
[0087] The polymerization reaction of the olefin monomer may be carried out by a conventional process applied to the polymerization of olefin monomers, such as continuous solution polymerization, bulk polymerization, suspension polymerization, slurry polymerization, or emulsion polymerization.
[0088] The polymerization reaction of the olefin monomer may be carried out in an inert solvent, and examples of the inert solvent include, but are not limited to, benzene, toluene, xylene, cumene, heptane, cyclohexane, methylcyclohexane, methylcyclopentane, n-hexane, 1-hexene, and 1-octene.
[0089] The polymerization of the olefin polymer may be carried out at a temperature of about 25° C. to about 500° C., specifically, at a temperature of 80° C. to 250° C., more preferably at a temperature of 100° C. to 200° C. The reaction pressure during polymerization is 1 kgf / cm. 2 ~150kgf / cm 2 , preferably 1kgf / cm 2 ~120kgf / cm 2 , more preferably 5kgf / cm 2 ~100kgf / cm 2 may be also possible.
[0090] Since the olefin polymer of the present invention has improved physical properties, it is useful for blow molding, extrusion molding, or injection molding in various fields and applications such as various packaging applications such as materials for automobiles, electric wires, toys, fibers, medical products, etc., construction, and daily necessities, and is particularly useful for automobiles where excellent impact strength is required.
[0091] The olefin polymer of the present invention can also be effectively used in the production of molded articles. Specifically, the molded product may be a blow molding product, an inflation molding product, a cast molding product, an extrusion laminate molding product, an extrusion molding product, a foam molding product, an injection molding product, a sheet, a film, a fiber, a monofilament, or a nonwoven fabric.
[0092] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a schematic diagram of a semiconductor device according to an embodiment of the present invention; EXAMPLES
[0093] Catalyst manufacturing example: Manufacturing of transition metal compounds [ka]
[0094] (1) Preparation of 2-methyl-7-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)indoline (i) Preparation of lithium carbamate 2-Methylindoline (98.24 mmol) and diethyl ether (150 mL) were placed in a Schlenk flask. The Schlenk flask was immersed in a -78 ° C cold bath made with dry ice and acetone and stirred for 30 minutes. Then, n-BuLi (98.24 mmol) was added with a syringe under a nitrogen atmosphere to form a pale yellow slurry. Then, the flask was stirred for 2 hours, and the temperature of the flask was raised to room temperature while removing the generated butane gas. The flask was again immersed in a -78 ° C cold bath to lower the temperature, and CO2 gas was added. By adding carbon dioxide gas, the slurry disappeared and a transparent solution was obtained. The flask was connected to a bubbler to remove carbon dioxide gas and the temperature was raised to room temperature. Then, excess CO2 gas and the solvent were removed under vacuum. The flask was transferred to a dry box, pentane was added, and the mixture was vigorously stirred and filtered to obtain lithium carbamate, a white solid compound. The white solid compound has diethyl ether coordinated thereto.
[0095] (ii) Preparation of 2-methyl-7-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)indoline The lithium carbamate compound (2.60 mmol) prepared in step (i) was placed in a Schlenk flask. Tetrahydrofuran (63.9 mmol) and 45 mL of diethyl ether were then added in that order. The Schlenk flask was immersed in a low-temperature bath at -20°C made of acetone and a small amount of dry ice, stirred for 30 minutes, and then t-BuLi (42.60 mmol) was added. At this time, the color of the reaction mixture changed to red. Stirring was continued for 6 hours while maintaining the temperature at -20°C. A CeCl3·2LiCl solution (42.60 mmol) dissolved in tetrahydrofuran and tetramethylcyclopentanone (42.60 mmol) were mixed in a syringe and then added to the flask under a nitrogen atmosphere. The temperature of the flask was gradually raised to room temperature, and after 1 hour, the thermostatic bath was removed and the temperature was maintained at room temperature. Water (15 mL) was then added to the flask, followed by ethyl acetate and filtration to obtain a filtrate. The filtrate was transferred to a separatory funnel, hydrochloric acid (2N, 80mL) was added, and the mixture was shaken for 12 minutes. Saturated aqueous sodium bicarbonate solution (160mL) was then added to neutralize the mixture, and the organic layer was extracted. Anhydrous magnesium sulfate was added to the organic layer to remove moisture, and the mixture was filtered, after which the filtrate was taken and the solvent was removed. The filtrate was purified by column chromatography using a solvent of hexane and ethyl acetate (v / v, 10:1) to obtain a yellow oil. The yield was 19%.
[0096] 1 H NMR(C6D6): δ6.97(d, J=7.2Hz, 1H, CH), δ6.78(d, J=8Hz, 1H, CH), δ6.67(t, J=7.4Hz, 1H, CH), δ3.94(m, 1H, quinoline-CH), δ3.51(br s, 1H, NH), δ3.24-3.08(m, 2H, quinoline-CH2, Cp-CH), δ2.65(m, 1H, quinoline-CH 2 ), δ1.89(s, 3H, Cp-CH3), δ1.84(s, 3H, Cp-CH3), δ1.82(s, 3H, Cp-CH3), δ1.13(d, J=6Hz, 3H, quinoline-CH3), δ0.93(3H, Cp-CH3)ppm.
[0097] (2) [(2-methylindolin-7-yl)tetramethylcyclopentadienyl-η 5 Production of [(2-Methylindolin-7-yl)tetramethylcyclopentadienyl-eta5, kapa-N]titanium dimethyl (i) 2-Methyl-7-(2,3,4,5-tetramethyl-1,3-cyclopentadienyl)-indoline (2.25 g, 8.88 mmol) and 140 mL of diethyl ether were placed in a round-bottom flask, the temperature was lowered to -30°C, and n-BuLi (17.6 mmol) was gradually added while stirring. The temperature was raised to room temperature and the reaction was carried out for 6 hours. After that, the mixture was washed several times with diethyl ether and filtered to obtain a solid. The remaining solvent was removed under vacuum, and a dilithium salt compound coordinated with diethyl ether (compound 4g) was obtained (1.37 g, 50%).
[0098] 1 H NMR(Pyridine-d8):δ7.22(br s, 1H, CH), δ7.18(d, J=6Hz, 1H, CH), δ6.32(t, 1H, CH), δ4.61(brs, 1H, CH), δ3.54(m, 1H , CH), δ3.00(m, 1H, CH), δ2.35-2.12(m, 13H, CH, Cp-CH3), δ1.39(d, indoline-CH3)ppm.
[0099] (ii) In a dry box, TiCl4·DME (4.44 mmol) and diethyl ether (150 mL) were placed in a round bottom flask, and while stirring at -30℃, MeLi (8.88 mmol) was gradually added. After stirring for 15 minutes, the dilithium salt compound (1.37 g, 4.44 mmol) prepared in step (i) was added to the flask. The temperature was raised to room temperature and stirring was continued for 3 hours. After the reaction was completed, the solvent was removed under vacuum, the solution was dissolved in pentane, and the filtrate was collected by filtration. The pentane was removed under vacuum to produce the titanium compound.
[0100] 1H NMR(C6D6): δ7.01-6.96(m, 2H, CH), δ6.82(t, J=7.4Hz, 1H, CH), δ4.96(m, 1H, CH), δ2.88(m, 1H, CH), δ2.40(m, 1H, CH), δ2.02(s, 3H, Cp-CH3), δ2 .01(s, 3H, Cp-CH3), δ1.70(s, 3H, Cp-CH3), δ1.69(s, 3H, Cp-CH3), δ1.65(d, J=6.4Hz, 3H, indoline-CH3), δ0.71(d, J=10Hz, 6H, TiMe2-CH3)ppm.
[0101] Examples and Comparative Examples: Production of Olefin Polymers Example 1 A 1.5L continuous process reactor was filled with hexane solvent (7 kg / h) and 1-butene (0.29 kg / h), and the temperature at the top of the reactor was preheated to 139.2°C. Triisobutylaluminum compound (TiBAl, 0.03 mmol / min), the transition metal compound (0.28 μmol / min) obtained in the above Preparation Example, and dimethylanilinium tetrakis(pentafluorophenyl)borate cocatalyst (0.87 μmol / min) were simultaneously added to the reactor. Then, hydrogen gas (33 cc / min) and ethylene (0.87 kg / h) were added to the reactor, and the copolymerization reaction was carried out at 139.2°C for 30 minutes or more in a continuous process at a pressure of 89 bar to obtain a copolymer. Then, the copolymer was dried in a vacuum oven for 12 hours or more, and the physical properties were measured.
[0102] Examples 2 to 5 Copolymers were obtained by carrying out the copolymerization reaction in the same manner as in Example 1, except that the production conditions were changed as shown in Table 1 below.
[0103] Comparative Example 1 DF840 manufactured by Mitsui Chemicals was purchased and used.
[0104] Comparative Example 2 DF810 manufactured by Mitsui Chemicals was purchased and used.
[0105] Comparative Example 3 Copolymers were obtained by carrying out the copolymerization reaction in the same manner as in Example 1, except that the production conditions were changed as shown in Table 1 below.
[0106] [Table 1]
[0107] Experimental Example 1: Analysis of olefin polymers The physical properties of the copolymers of the above Examples and Comparative Examples were evaluated by the following methods and are shown in Table 2 below.
[0108] (1) Density Measured according to ASTM D-792. (2) Melt Index (MI) Measurement was performed according to ASTM D-1238 (condition E, 190°C, 2.16 kg load).
[0109] (3) Melt flow rate ratio (MFRR, Melt flow rate ratio, MI 10 / MI 2.16 ) ASTM D-1238 [Condition E, MI 10 (190℃, 10kg load), MI 2.16 (190℃, 2.16kg load)] according to MI 10 and M.I. 2.16 After measuring, MI 10 MI 2.16 The melt flow rate ratio was calculated by dividing the melt flow rate by the melt flow rate. (4) Weight average molecular weight (Mw, g / mol) and molecular weight distribution (MWD) The number average molecular weight (Mn) and weight average molecular weight (Mw) were measured by gel permeation chromatography (GPC), and the molecular weight distribution was calculated by dividing the weight average molecular weight by the number average molecular weight.
[0110] -Column: PL Olexis -Solvent: TCB (trichlorobenzene) -Flow rate: 1.0ml / min -Sample concentration: 1.0mg / ml -Injection volume: 200μl -Column temperature: 160℃ -Detector: Agilent High Temperature RI detector -Standard: Polystyrene (corrected by a cubic function)
[0111] (5) Melting temperature (Tm) and glass transition temperature (Tg) The results were obtained using a TA Instruments Differential Scanning Calorimeter (DSC: Differential Scanning Calorimeter 250). That is, the temperature was increased to 150°C, maintained at that temperature for 1 minute, then decreased to -100°C, and the temperature was increased again to observe the DSC curve.
[0112] (6)P(50), P(70), elution temperature (Te) As a measuring device, a CFC manufactured by PolymerChar was used. First, the polymer solution was completely dissolved in an oven in a CFC analyzer at 130°C for 60 minutes using o-dichlorobenzene as a solvent, and then introduced into a TREF column adjusted to 135°C, cooled to 95°C, and stabilized for 45 minutes. Next, the temperature of the TREF column was cooled to -20°C at a rate of 0.5°C / min, and then maintained at -20°C for 10 minutes. Then, the elution amount (mass%) was measured using an infrared spectrophotometer. Next, the temperature of the TREF column was increased to a preset temperature at a rate of 20°C / min, and the temperature was maintained at the temperature reached for a preset time (i.e., about 27 minutes). This operation was repeated until the temperature of the TREF reached 130°C, and the amount (mass%) of the fraction eluted during each temperature range was measured. In addition, the fractions eluted at each temperature were sent to a GPC column, and the weight average molecular weight (Mw) was measured in the same manner as in the GPC measurement principle, except that o-dichlorobenzene was used as the solvent.
[0113] When a temperature-dissolution amount graph was drawn and integrated to standardize the total dissolution amount to 100%, the amount (wt%) dissolves at -20 to 50°C was defined as P(50), and the amount (wt%) dissolves at -20 to 75°C was defined as P(75). Additionally, the elution temperature (Te) refers to the temperature corresponding to the highest point of the peak present after -20°C in the graph.
[0114] (7)Soluble Fraction The content of the soluble fraction (SF) means the content of the fraction eluted at -20°C or lower, and was measured using CFC.
[0115] [Table 2]
[0116] As shown in Table 2, the olefin-based copolymers according to the examples satisfy the requirements (1) to (4) defined in the present invention, whereas the comparative examples do not satisfy the requirements. In particular, the P(75)-P(50) value is very small, being less than 8.0.
[0117] Experimental Example 2: Evaluation of olefin polymers The physical properties of the olefin-based polymers of the above Examples and Comparative Examples were measured by the following methods.
[0118] (1) Tensile strength and elongation Each copolymer was extruded into pellets, and the tensile strength and elongation at break were measured according to ASTM D638 (500 mm / min).
[0119] (2) Tear strength Each copolymer was extruded into pellets, and the tear strength at break was measured according to D624 (Type C).
[0120] (3) Flexural modulus Measurements were performed according to ASTM D790 using an INSTRON 3365 instrument.
[0121] (4) Hardness (shore A) The hardness was measured according to the ASTM D2240 standard using a TECLOCK GC610 STAND for Durometer and a Mitutoyo Shore hardness tester Type A.
[0122] [Table 3]
[0123] As shown by the above results, it was confirmed that the olefin-based polymers of the Examples had increased mechanical rigidity, and had increased tensile strength, tear strength, flexural modulus, hardness, etc., compared to the Comparative Examples.
Claims
1. An olefin-based polymer satisfying the following requirements (1) to (4) and (10): (1) A melt index (Melt Index, 190° C., 2.16 kg load condition) of 0.1 to 10.0 g / 10 min; (2) the density is 0.875 to 0.895 g / cc; (3) the elution temperature (Te) measured by cross-fractionation chromatography (CFC) is 30 to 40°C; (4) When CFC is measured, 8.0≦P(75)−P(50)≦12.0; Here, P(75) and P(50) are the elution amounts (wt%) in the temperature range of −20 to 75° C. and −20 to 50° C. in the temperature-elution amount graph measured by CFC, respectively; (10) The soluble fraction (SF) at -20°C is 2% by weight or less when measured by cross fractionation chromatography (CFC).
2. The olefin-based polymer according to claim 1, further satisfying the following requirement (5): (5) Melt flow rate ratio (MFRR, Melt flow rate ratio, MI 10 / M.I. 2.16 ) is between 5 and 10.
3. The olefin-based polymer according to claim 1 or 2, further satisfying the following requirement (6): (6) The melting temperature (Tm) measured by differential scanning calorimetry (DSC) is 55 to 90°C.
4. The olefin-based polymer according to any one of claims 1 to 3, further satisfying the following requirement (7): (7) The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is −70 to −30° C.
5. The olefin-based polymer according to any one of claims 1 to 4, further satisfying the following requirement (8): (8) The weight average molecular weight is 10,000 to 500,000 g / mol.
6. The olefin-based polymer according to any one of claims 1 to 5, further satisfying the following requirement (9): (9) The molecular weight distribution (MWD) is 0.1 to 6.
0.
7. The olefin polymer according to any one of claims 1 to 6, which is a copolymer of ethylene and an α-olefin comonomer having 3 to 12 carbon atoms.
8. The olefin polymer according to claim 7, wherein the α-olefin comonomer is at least one selected from the group consisting of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, and 1-dodecene.
9. The olefin polymer according to claim 7, which is a copolymer of ethylene and 1-butene.
Citation Information
Patent Citations
Olefin polymers and methods for producing the same
JP2013533351A
Method for preparing olefin polymer using transition metal catalyst having better copolymerization
KR101066969B1
KR2007-0003071